Implementasi Algoritma Luc Pada Aplikasi Keamanan Short Message Service (SMS) Berbasis Android - Yusuf Anshori; Deny Wiria Nugraha; Arief Pratomo (CESS (Journal of Computer Engineering, System and Science), 2021)
Short Message Service (SMS) still has security problems with attempts to steal messages, intercept messages, hijack messages by parties who are not responsible for obtaining information. Cryptography is the science of maintaining the confidentiality of information from aspects that can threaten information security with certain mathematical algorithms and techniques. The Luc algorithm is a public key cryptographic algorithm that was developed using the lucas function. This study aims to implement the Luc algorithm on an Android-based SMS security application in the National Narcotics Agency of Central Sulawesi Province to maintain privacy in communication between the sender and recipient of the message. This application was created using an Android studio developer with the Java programming language. Based on the results of the first test for a sample of plain messages in the word KOTA PALU that uses public key 13 produces the message cipher P=Se!CQa. The second test result for the message sample on the word KOTA PALU that uses public key 29 generates the AD*`_$(NQ cipher message